Composição química e digestibilidade in vitro da massa seca de cana-de-açúcar acrescida de ureia em diferentes tempos de estocagem - de Rezende, Adauton Vilela (2012)
The objective of this research was to evaluate the chemical composition and in vitro dry mass (DM) digestibility of sugar cane with urea, maintained in the shade and sun, at different storage times. The utilized design was the completely randomized in a factorial scheme 6x2, that is, six storage times after the mixing (0; 2; 4; 6; 12 and 24 hours) and two storage location (shade and sun), with three replicates. The sugarcane utilized presented 12 months of development and was disintegrated for application of mixture (nine parts of urea for one of ammonium sulfate) to 1.0kg/100.0kg of fresh sugarcane. The samples taken with 12 hours of storage indicated that was an increase in the content of DM and crude protein (CP) of sugar cane compared to the moment of the mixture (307.6 vs. 294.2g/kg of DM and 115.2 vs. 99.3 g/kg of DM, respectively), and the smaller content of neutral detergent fiber (NDF) was observed around of 12 hours of storage (465.0g/kg of DM). The coefficients of in vitro dry mass digestibility (IVDMD) ranged of 0.558 to 0.612 in the times 0 and 12 hours, respectively. The length of storage changes the chemical composition of sugar cane plus urea. The storage location changes the dry mass content and pH values.